Burkholderia pseudomallei biofilm phenotypes confined but surviving in neutrophil extracellular traps of varying appearance - Khamwong, Muthita; Phanthanawiboon, Supranee; Salao, Kanin; Chareonsudjai, Sorujsiri (Frontiers in Immunology, 2022)
Melioidosis is a fatal infectious disease caused by Burkholderia pseudomallei. Complications following treatment are usually due to antibiotic resistance and relapse is mainly caused by B. pseudomallei biofilm. Although the release of neutrophil extracellular traps (NETs) is crucial to capture and eliminate bacterial pathogens, to date response of NETs to B. pseudomallei biofilm is poorly understood. Here we compare the NETs produced by neutrophils in response to B. pseudomallei H777 (a biofilm-producing strain containing the bpsl0618 gene), a biofilm-defect strain lacking this gene (B. pseudomallei M10) and a bpsl0618 biofilm-complemented strain, B. pseudomallei C17, in which function of bpsl0618 was restored. Co-cultivation of these strains with healthy human neutrophils at MOI 10 with or without cytochalasin D demonstrated that H777 significantly resisted neutrophil-mediated killing and non-phagocytotic mechanisms compared to M10 (p < 0.0001). Three distinct morphotypes of NETs were seen: “aggregated”, “spiky” and “cloudy”. These were induced in different proportions by the different bacterial strains. All types of NETs were shown to confine all B. pseudomallei strains. Strains H777 and C17 could stimulate production of twice as much extracellular DNA (234.62 ng/ml and 205.43 ng/ml, respectively) as did M10 (111.87 ng/ml). Cells of H777 and C17 were better able to survive in the presence of neutrophil killing mechanisms relative to M10 (p < 0.0001) and NET formation (p < 0.0001 and 0.05). These findings suggest that NET stimulation was insufficient to eradicate B. pseudomallei H777 and C17 despite their possession of bpsl0618, a sugar-transferase gene associated with biofilm formation ability. Our findings demonstrate that B. pseudomallei biofilm phenotype may be a key factor in assisting pathogens to escape killing by neutrophils. This work provides a better understanding of how B. pseudomallei biofilm-associated infections induce and survive NET formation, resulting in bacterial persistence and increased severity of disease.